Kolaborasi Pencegahan Dan Penanggulangan Covid-19 Di Kota Baubau - Zainul Abidin; Nurhayati Nurhayati; La Didi; Suharny Suharny (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to describe the collaboration for the prevention and control of COVID-19 in Baubau City. This research is important because there are problems in the dynamics of collaboration, especially related to maintenance, as well as to describe the uniqueness that occurs. The research design used was qualitative with a descriptive approach. Data collection techniques using observation, interviews, and documents. The data analysis technique uses an interactive model. The results of the study show that community-based collaboration has been implemented, especially in Wajo and Lakologou Villages through the construction of tough villages by having order and security toughness, information resilience, psychological toughness and cultural toughness. There is also maintenance or system maintenance. However, the maintenance or maintenance of tough villages in Lakologou Village has stronger characteristics and has more potential for sustainability. The collaboration that occurs is able to bring in new contributors, social capital and condition sustainability. A tough village with its various tools should be maintained and even improved for other interests in the future.